Oral Probiotic VSL#3 Prevents Autoimmune Diabetes by Modulating Microbiota and Promoting Indoleamine 2,3-Dioxygenase-Enriched Tolerogenic Intestinal Environment - Falcone, Marika; Canducci, Filippo; Saita, Diego; Ferrarese, Roberto; Cosorich, Ilaria; Di Pietro, Caterina; Sorini, Chiara; Dolpady, Jayashree; Clementi, Massimo (Journal of Diabetes Research, 2016)
The gut microbiota modulates the autoimmune pathogenesis of type 1 diabetes (T1D) via mechanisms that remain largely unknown. The inflammasome components are innate immune sensors that are highly influenced by the gut environment and play pivotal roles in maintaining intestinal immune homeostasis. In this study we show that modifications of the gut microbiota induced by oral treatment with Lactobacillaceae-enriched probiotic VSL#3, alone or in combination with retinoic acid (RA), protect NOD mice from T1D by affecting inflammasome at the intestinal level. In particular, we show that VSL#3 treatment inhibits IL-1β expression while enhancing release of protolerogenic components of the inflammasome, such as indoleamine 2,3-dioxygenase (IDO) and IL-33. Those modifications of the intestinal microenvironment in VSL#3-treated NOD mice modulate gut immunity by promoting differentiation of tolerogenic CD103+ DCs and reducing differentiation/expansion of Th1 and Th17 cells in the intestinal mucosa and at the sites of autoimmunity, that is, within the pancreatic lymph nodes (PLN) of VSL#3-treated NOD mice. Our data provide a link between dietary factors, microbiota composition, intestinal inflammation, and immune homeostasis in autoimmune diabetes and could pave the way for new therapeutic approaches aimed at changing the intestinal microenvironment with probiotics to counterregulate autoimmunity and prevent T1D.